Designing with and for people with dementia: developing a mindful interdisciplinary co-design methodology - Niedderer, Kristina; Tournier, Isabelle; Coleston-Shields, Donna Maria; Craven, Michael P.; Gosling, Julia A.; Garde, J; Salter, Ben; Bosse, Mochaelle; Griffoen, Ingeborg (2017)
This paper reports on the development of a mindful interdisciplinary design methodology in the context of the MinD project research into designing for and with people with dementia, which takes the particular focus on supporting the subjective well-being and self-empowerment of people with early to mid stage dementia in social context. Existing research is for the most part focussed on functional support and safe-keeping from the perspective of the carer. References to decision-making and empowerment are predominantly related to action planning for dementia care or advance care planning. References to care and social interaction show that caregivers tend to take a deficit-oriented perspective, and occupation of people with dementia is often associated with doing 'something' with little focus on the meaningfulness of the activity. Furthermore, caregivers and people with dementia tend to differ in their perspectives, e.g. on assistive devices, which might offer support. The MinD project, has therefore developed an interdisciplinary co-design methodology in which the voices to people with dementia contribute to better understanding and developing mindful design solutions that support people with dementia with regard to their the subjective well-being and self-empowerment a well as meaningful and equitable social engagement. This paper discussed the design methodological framework and methods developed for the data collection and design development phases of the project, and their rationale. It thus makes a contribution to interdisciplinary methodologies in the area of design for health.